3D Finite Element Model and Measurement Comparison for Roller Compaction Ιnduced Vibration: The Case Study of a Ring Road in Hanoi, Vietnam - Nguyen, Ngoc Long; Nguyen, Chau Lan; Bui, Tien Thanh; Dang, Lam Hong (Engineering, Technology & Applied Science Research, 2023)
Vietnam is currently constructing many transportation and infrastructure projects in urban areas. During the construction process of road foundations such as pile driving and vibratory compaction often causes vibrations that can affect nearby structures. Therefore, it is necessary to study the impact of vibrations induced by construction activities. A study was conducted to investigate the impact of roller compaction-induced vibration on the buildings and structures of Ring Road No.2 in Hanoi, Vietnam. The study also applied a 3D FEM method to evaluate the impact of vibration on surrounding structures. The results showed a good correlation between finite element calculations and field measurements.